Intracystic Papillary Carcinoma in the Male Breast: A Rare Endpoint of a Wide Spectrum - Ketan Vagholkar; Khojasteh Dastoor; Indumati Gopinathan (Case Reports in Oncological Medicine)
Introduction. Fibrocystic disease of the male breast is uncommon. The presence of a spectrum of changes ranging from fibrocystic disease to duct papilloma to papillary carcinoma in the same patient renders the case a rarity and therefore reportable. Case Report. A case of intracystic papillary carcinoma of the male breast is presented. Discussion. The pathological, clinical, diagnostic, and therapeutic options are discussed after reviewing the literature. Conclusion. Modified radical mastectomy with axillary clearance is the safest option for established cases.